Easy‐to‐Implement Ultra‐Thin, Wide‐Band, and Multi‐Functional Polarization Converter for K and Ka Band Applications. Issue 4 (20th February 2022) - Coskun, Aykut; Hasar, Ugur Cem; Ozmen, Ahmet; Ertugrul, Mehmet
Abstract: This article presents an ultrathin, broadband, and multipurpose polarization converter design utilizing an anisotropic metasurface for K and Ka band. The proposed polarization converter, which has a single layer F4B as a substrate material with hexagonal‐shaped metallic solid structure along with hexagonal ring with diagonal splits on its front surface and a background (a completely metallic surface) on its back, works as not only a circular polarization converter but also a linear polarization to circular polarization (LP to CP) converter. Its polarization conversion rate (PCR) is more than 90% in the frequency range from 17.87 to 43.15 GHz, covering all of the K and Ka bands with a relative bandwidth of 83% under normal incidence case. For incidence angles up to 40°, PCR is observed to be greater than 75% in almost all of the K and Ka bands (except for the frequency range between 24.72 and 27.11 GHz). Furthermore, the proposed design has LP to CP in two different frequency bands, 16.23–16.74 GHz and 48.6–48.8 GHz. The proposed polarization converter, as advantages, is low cost, ultra thin, broadband, and facile, which can be useful in linear cross polarization conversion in K and Ka band applications. Abstract : This article presents an ultrathin, broadband, and multipurpose polarization converter design for K and Ka band. Its polarization conversion rate (PCR) is more than 90% in the frequency range from 17.87 to 43.15 GHz. Furthermore, the proposed design has linear polarization to circular polarization in 16.23–16.74 GHz and 48.6–48.8 GHz.